Unlocking Landscapes Through Westonbirt’s Archive - Clare Hickman; Sarah Bell (Plant Perspectives)
There are growing calls across research, policy and practice to enable historic designed landscape experiences – from country estate gardens through to public parks and arboretums – that are accessible and engaging for all. In this paper, we highlight how meaningful access reaches beyond measures to enable physical presence in a landscape to the ways in which such landscapes, and human-plant relationships, are storied and interpreted, ensuring that people can also identify as part of the evolving stories of such places. Using twentieth century archival sources, particularly the diaries of foresters, held on site at Westonbirt, the National Arboretum in Gloucestershire, UK, we suggest ways in which sensory history approaches can be used to bring greater depth, context and diversity to historic designed landscape interpretation. Applying these approaches to archival research offers the potential to broaden the stories shared about such landscapes, enabling people to learn about and relate to the varied social and sensory histories of these significant places, plants and the people that shaped them.